just substitute 3a-1 for f(a) and x-2 for g(a):
2(3a-1) - 3(a-2) = 5
6a - 2 - 3a + 6 = 5
3a + 4 = 5
3a = 1
a = 1/3
you do the next one ...
2006-10-14 15:24:29
·
answer #1
·
answered by oh so blue 3
·
1⤊
0⤋
Its very simple.
Solution for (a)
2f(a)-3g(a)=5
now replace values of f(a)= 3a-1 and g(a)=a-2
=> 2(3a-1) -3 (a-2) = 5
=>6a-2 -3a +6 = 5
=>3a + 4 = 5
=> 3a = 1
=>a = 1/3
solution (b)
f(2b) - g(3b) = 5
replace original values of x in f(x) & g(x) with 2b & 3b respectively. And we get,
=>[3(2b)-1] - [3b-2] = 5
=>6b -1 - 3b +2 = 5
=> 3b + 1 = 5
=> 3b = 4
=>b = 4/3
Hey, let me know if this answers were correct.
2006-10-14 22:29:53
·
answer #2
·
answered by Hiren 1
·
0⤊
0⤋
This is functional notation. When you have something like f(x)=3x-1, that's just a mathematical way of saying taking x, multiply it by 3, subtract one and the result is called f(x). If x is a particular real number, then you can calculate f(x) for that number.
Let me walk you through how to do these problems.
(a) 2f(a)-3g(a)=5
using f(x) and g(x) as defined means
f(a) = 3a-1 and g(a) = a-2
so the equation becomes
2(3a-1)-3(a-2) = 5
6a-2-3a+6=5
3a=1
a=1/3
(b) f(2b) = 3(2b)-1 = 6b-1
g(3b) = 3b-2
f(2b)-g(3b)=5
6b-1-(3b-2)=5
6b-1-3b+2=5
3b=4
b=4/3
Hope that helps you see how to do these!
2006-10-14 22:27:19
·
answer #3
·
answered by just♪wondering 7
·
0⤊
0⤋
Let f(x)=3x-1 and g(x)=x-2
(a) If 2f(a)-3g(a)=5ï¼find the value of a
2*(3a-1)-3*(a-2)=5
6a-2-3a+6=5
3a+4=5
3a=1
a=1/3
f(x)=3x-1 and g(x)=x-2
(b) If f(2b)-g(3b)=5ï¼find the value of b
(3*2b-1)-(3b-2)=5
6b-1-3b+2=5
3b+1=5
3b=4
b=4/3
2006-10-14 22:39:40
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
QUESTION
Let f(x)=3x-1 and g(x)=x-2
(a) If 2f(a)-3g(a)=5ï¼find the value of a
(b) If f(2b)-g(3b)=5ï¼find the value of b
SOLUTION
f(x)=3x-1 therefore f(a)=3a-1 2f(a) = 6a-2
g(x)=x-2 therefore g(a) = a-2 3g(a) = 3a-6
Given 2f(a)-3g(a)=5;
6a-2-(3a-6)=5 Expanding 6a-2-3a+6= 5
Hence 3a=1
a= 1/3
f(x)=3x-1 therefore f(2b)= 6b-1 in place of x substitute 2b
g(x)=x-2 therefor g(3b) = 3b-2 In place of substitute 3b
Given
f(2b)-g(3b)=5 Hence 6b-1 -(3b-2)=5
6b-1-3b+2=4
6b-3b=4+1-2
3b=3
b=1
2006-10-14 22:36:44
·
answer #5
·
answered by Willy Brown 2
·
0⤊
0⤋
for me the equations are....
(a) solve for a...
2(3a-1)-3(a-2)= 5
6a-2-3a+6=5
6a-3a+4=5
3a=5-4
3a=1
a=1/3
(b)solve for b...
2(3b-1)-3(b-2)=5
6b-2-3b+6=5
3b+4=5
3b=5-4
3b=1
b=1/3
that's all... very simple
2006-10-15 07:12:27
·
answer #6
·
answered by mich 2
·
0⤊
0⤋
Just replace what is inside the f(), for the x variable of it.
For example:
a) 2 * f(a) - 3 * g(a) = 5
2 * f(3a-1) - 3 * g(a-2) = 5
2(3a-1) - 3(a-2) = 5
6a-2 -3a+2 = 5
3a = 5
a = 5/3
2006-10-14 22:22:54
·
answer #7
·
answered by icez 4
·
0⤊
0⤋
Just plug and chug..
put a into f(x) and g(x)
put those expressions into the big equation:
2(3a-1)-3(a-2) = 5
Now just collect terms and solve for a
Same thing on b, sort of. a little trickier though
2006-10-14 22:22:25
·
answer #8
·
answered by modulo_function 7
·
0⤊
0⤋
Is this homework from Crazy Math 101 ?
2006-10-15 02:29:44
·
answer #9
·
answered by PC_Load_Letter 4
·
0⤊
0⤋